Ageing patients in forensic psychiatric settings: a review of the literature - Di Lorito, Claudio; Völlm, Birgit; Dening, Tom (Wiley, 2018)
Objectives. The prevalence of ageing patients in forensic psychiatric settings is increasing. However, limited research has reported around this population. The aim of this scoping review is to synthesise the current evidence around ageing forensic psychiatric patients.